Towards a Jurisprudence of the Embodied mind – Sarah Lund, Forbrydelsen and the Mindful Body - Leiboff, Marett (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
As Erika Fischer-Lichte remarked, the great Polish theatre theorist Jerzy Grotowski redefined the notion of the body of the actor as an embodied mind, as a responsive and responding self. Conversely, law abjures the body, its interpreters – lawyers and scholars – inured in practices of rationality, reason and logic, or mindful disembodiment. Travelling through the Danish capital, encountering Danes real and fictitious to illustrate how much we function through our bodies, this essay suggests that we are better and more effective legal interpreters as embodied minds, rather than disembodied minds. But this is not mindless embodiment, a mere reflex or bodily outburst. The embodied mind is self-aware (physically, socially, intellectually) and possesses the same embodied virtuous morality held by Grotowski’s actors. Reminiscent of Kierkegaard’s uniting of the mind-body divide, this connected mind and body challenges the Augustinian negation of the body and associated interpretative assumptions inherited over centuries of legal thought.